Dynamics of microbiota and physicochemical characterization of food waste in a new type of composter - Gaspar, Suelen S.; Assis, Lucas L. R.; Carvalho, Carla A.; Buttrós, Victor Hugo; Ferreira, Gustavo Magno dos Reis; Schwan, Rosane F.; Pasqual, Moacir; Rodrigues, Filipe Almendagna; Rigobelo, Everlon Cid; Castro, Rafael Peron; Dória, Joyce (Frontiers in Sustainable Food Systems, 2022)
Organic wastes are considered the most significant components of urban solid waste, negatively affecting the environment. It is essential to use renewable resources to minimize environmental risks. Composting is one of the most sustainable methods for managing organic waste and involves transforming organic matter into a stable and nutrient-enriched biofertilizer, through the succession of microbial populations into a stabilized product. This work aimed to evaluate the efficiency of the new type of composter and the microbial and physiochemical dynamics during composting aiming to accelerate the degradation of organic waste and produce high-quality compost. Two inoculants were evaluated: (1) efficient microorganisms (EM); (2) commercial inoculum (CI), which were compared to a control treatment, without inoculation. Composting was performed by mixing organic waste from gardening with residues from the University's Restaurant (C/N ratio 30:1). The composting process was carried out in a 1 m3 composter with controlled temperature and aeration. The thermophilic phase for all treatments was reached on the second day. Mature compost was obtained after an average of 120 days, and composting in all treatments showed an increase in the availability of P and micronutrients. The new composter helped to accelerate the decomposition of residues, through the maintenance of adequate oxygen content and temperature control inside the cells, providing high metabolic activity of microorganisms, contributing to an increase in physicochemical characteristics, also reducing the composting time in both treatments. During composting, the bacteria and actinobacteria populations were higher than yeasts and filamentous fungi. The inoculated treatments presented advantages showing more significant mineralization of P-available and micronutrients such as Mn and Zn in terms of the quality of the final product in comparison to the control treatment. Finally, the new composter and the addition of inoculants contributed significantly to the efficiency of the process of composting organic waste.